2019
DOI: 10.1111/eva.12872
|View full text |Cite
|
Sign up to set email alerts
|

The type of bottleneck matters: Insights into the deleterious variation landscape of small managed populations

Abstract: Predictions about the consequences of a small population size on genetic and deleterious variation are fundamental to population genetics. As small populations are more affected by genetic drift, purifying selection acting against deleterious alleles is predicted to be less efficient, therefore increasing the risk of inbreeding depression. However, the extent to which small populations are subjected to genetic drift depends on the nature and time frame in which the bottleneck occurs. Domesticated species are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…We used a dataset by Bortoluzzi and colleagues available at the European Nucleotide Archive (http://www.ebi.ac.uk/ena/) under accession number PRJEB34245 [31] and PRJEB36674 [18]. The dataset comprised a total of 169 individuals sampled from 88 traditional chicken breeds of divergent demographic and selection history.…”
Section: Chicken Genomic Datamentioning
confidence: 99%
“…We used a dataset by Bortoluzzi and colleagues available at the European Nucleotide Archive (http://www.ebi.ac.uk/ena/) under accession number PRJEB34245 [31] and PRJEB36674 [18]. The dataset comprised a total of 169 individuals sampled from 88 traditional chicken breeds of divergent demographic and selection history.…”
Section: Chicken Genomic Datamentioning
confidence: 99%
“…The hypothesis that the type and time-frame of a population decline have important consequences on a population's genetic variation was more formally analysed in local chicken breeds by Bortoluzzi et al (2020) (Chapter 3). In fact, the authors showed that populations that remained small for a long period of time have been able to minimize the effects of genetic drift on the deleterious variation contrary to recently bottlenecked populations that are more susceptible to genetic stochasticity [25]. These conclusions have important implications for management, as also illustrated in recent simulations of Kyriazis et al (2019).…”
Section: Functional Evaluation Of Genetic Diversity 131 Deleteriousmentioning
confidence: 91%
“…Over time, if unrestrained, the amount of genetic variation necessary for adaptation is expected to erode, taking a population (or species) to the brink of extinction [162]. Although the effects of genetic drift on individual genomes have been thought to be gradual, recent studies have shown that the response of a population to genetic drift depends on the type and time-frame of the bottleneck [25] (Chapter 3), the (long-term) persistence of a population small in size [174,256], and the presence of a conservation programme [1,28] (Chapter 4).…”
Section: Genetic Driftmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be inferred by quantifying homozygous stretches in the genome called runs of homozygosity (ROH). ROHs are enriched for homozygous deleterious variants (Bortoluzzi et al 2019), and therefore is useful as indicator for inbreeding risk. While both methods can provide accurate estimates of the deleterious load, it usually does not provide any lead to the effects of any particular deleterious variants, nor does it indicate which variants contribute to the negative fitness effects in inbred populations (if present).…”
Section: Deleterious Allelesmentioning
confidence: 99%